Sporadic rainy events are more critical than increasing of drought intensity for woody species recruitment in a Mediterranean community. - Matías, Luis; Zamora, Regino; Castro, Jorge (Oecologia, 2012)
The understanding of the impact of extreme climatic events under a global climate change scenario is crucial for the accurate forecast of future plant community dynamics. We have experimentally assessed the effect of drier and wetter summer conditions on the recruitment probabilities and the growth of seedlings from eight woody species representative of the most important functional groups in the community, pioneer shrubs, mid-successional shrubs and trees, across the main habitats in the study area (open habitat, shrubland, and forest). Our hypothesis proposes that wet summer conditions would represent a good opportunity for tree species regeneration, enhancing both forest maintenance and expansion. A drier summer scenario, on the other hand, would limit forest regeneration, and probably hinder the colonization of nearby habitats. We found a habitat effect on the emergence, survival, and final biomass, whereas different climate scenarios affected seedling survival and biomass. A wet summer boosted growth and survival, whereas greater drought reduced survival only in some cases. These results were modulated by the habitat type. Overall, shrub species presented higher survival and growth and were less affected by more severe drought, whereas some tree species proved to be extremely dependent on wet summer conditions. We conclude that the reduction in frequency of wet summers predicted for the coming decades in Mediterranean areas will have greater consequences for species recruitment than will increased drought. The different response of the species from the various functional groups has the potential to alter the composition and dominance of future plant communities.
Keywords: Angiosperms; Angiosperms: growth & development; climate change; Droughts; Ecosystem; Mediterranean Region; Rain; rainfall variability; Recruitment; Seedling; Seedling: growth & development; Spain; summer drought; Vegetation dynamics